2011
DOI: 10.1089/end.2010.0732
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Treatment Strategy Used During Shockwave Lithotripsy to Maximize Stone Fragmentation Efficiency

Abstract: A pretreatment dose of 100 low-voltage output shockwaves (SWs) at 60 SWs/min before increasing to a higher voltage output produces the best overall stone fragmentation in vitro. These findings could lead to increased fragmentation efficiency in vivo and higher success rates clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…A previous study of Korean patients reported no significant difference in SFRs according to output voltage [13]. Although the reason for negative results in the two aforementioned studies [12,13] remains unclear, different study protocols, including voltage setting, shockwave numbers at low voltage, and frequency, may have contribute to conflicting results among the studies [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A previous study of Korean patients reported no significant difference in SFRs according to output voltage [13]. Although the reason for negative results in the two aforementioned studies [12,13] remains unclear, different study protocols, including voltage setting, shockwave numbers at low voltage, and frequency, may have contribute to conflicting results among the studies [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 96%
“…Table 3 summarizes the results of published studies. In vitro [7,8], animal [9], and two clinical studies [10,11] showed improved stone fragmentation with voltage escalation compared to constant or decreasing voltage. Demirci et al [10] reported a significantly higher SFR at 8 weeks after single or multiple session of SWL in the escalating voltage group compared to the fixed voltage group.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations